Influence of Xpand Nitric Oxide Reactor, L-Arginine Alpha-Ketoglutarate, and Caffeine Supplementation on Calf Muscle Re-Oxygenation During and after Acute Resistance Exercise - Collins, Brittany C.; Sapp, Ryan; LaManca, John; Wolff, Christopher; Miranda, Edwin; Gutierrez, Vincent; Mazzetti, Scott A. (Journal of Nutritional Therapeutics, 2013)
Xpand Nitric Oxide Reactor is a ‘cocktail’ supplement proposed to improve skeletal muscle blood flow via arginine’s effect on nitric oxide synthesis and vasodilation. Two other major ingredients, caffeine and creatine, cause vasoconstriction, which could potentially counteract the proposed hemodynamic effects of arginine. The purpose of this study was to examine the influence of Xpand Nitric Oxide Reactor on muscle re-oxygenation after resistance exercise compared to supplementation with constituent ingredients L-arginine alpha-ketoglutarate and caffeine. Nine recreationally active men (21±1y) performed 3 sets of 20 repetitions of seated single-leg calf raise at 60% 1-RM with 3 min rests. The same calf raise exercise was performed following 4 separate supplementation conditions: L-arginine alpha-ketoglutarate (AAKG), caffeine (CAFF), Xpand Nitric Oxide Reactor (XPAND), and placebo (PLAC). Soleus muscle re-oxygenation time was measured before, during, and immediately after exercise using near infrared spectroscopy. Supplementation with XPAND (0.43±0.03), AAKG (0.34±0.02), and CAFF (0.45±0.05) did not significantly affect muscle re-oxygenation halftime (minutes) compared to placebo (0.35±0.04). An arginine containing ‘cocktail’ supplement did not affect skeletal muscle re-oxygenation after resistance exercise, possibly due to a wash-out effect caused by the multiple ingredients.